1997
DOI: 10.1128/mcb.17.9.5077
|View full text |Cite
|
Sign up to set email alerts
|

RRB1 and RRB2 Encode Maize Retinoblastoma-Related Proteins That Interact with a Plant D-Type Cyclin and Geminivirus Replication Protein

Abstract: Unlike mammalian and yeast cells, little is known about how plants regulate G 1 progression and entry into the S phase of the cell cycle. In mammalian cells, a key regulator of this process is the retinoblastoma tumor suppressor protein (RB). In contrast, G 1 control in Saccharomyces cerevisiae does not utilize an RB-like protein.We report here the cloning of cDNAs from two Zea mays genes, RRB1 and RRB2, that encode RB-related proteins. Further, RRB2 transcripts are alternatively spliced to yield two proteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
189
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(195 citation statements)
references
References 68 publications
5
189
0
1
Order By: Relevance
“…The alternating Leu, Cys and Glu residues point towards the inner part of the groove, making contacts with specific non-contiguous pRb residues. These residues are extremely conserved between pRb and pRb-like proteins of different species (Ach et al, 1997;Lee et al, 1998;Lu and Horvitz, 1998), indicating that this conserved groove of the B-box should play a critical role for the function of pRb, p107 and pRb2/p130.…”
Section: Adenovirus Early-region 1amentioning
confidence: 99%
“…The alternating Leu, Cys and Glu residues point towards the inner part of the groove, making contacts with specific non-contiguous pRb residues. These residues are extremely conserved between pRb and pRb-like proteins of different species (Ach et al, 1997;Lee et al, 1998;Lu and Horvitz, 1998), indicating that this conserved groove of the B-box should play a critical role for the function of pRb, p107 and pRb2/p130.…”
Section: Adenovirus Early-region 1amentioning
confidence: 99%
“…The requirement for RB in cell differentiation therefore extends beyond regulation of cell cycle entry. For example, the loss of RB function in cardioblasts affects cell differentiation by modulating the activity of cardiogenic factors (Papadimou et al, 2005).RB-related genes, termed RETINOBLASTOMA-RELATED (RBR; Ach et al, 1997), are also found in monocots (Grafi et al, 1996;Xie et al, 1996;Ach et al, 1997) and dicots (Nakagami et al, 1999;Kong et al, 2000) and even in unicellular algae (Umen and Goodenough, 2001). Animal pRb and plant RBR are similar in sequence and predicted protein structure and, thus, likely share similar functions (Flemington et al, 1993;Ramirez-Parra et al, 2003;Gruissem, 2007).…”
mentioning
confidence: 99%
“…AL1 and AL3 interact with the retinoblastoma-related protein (pRBR), a negative regulator of cell cycle progression and a differentiation factor (Weinberg, 1995;Ach et al, 1997;Kong et al, 2000). The AL1-pRBR interaction interferes with pRBR binding to the cell cycle-associated E2F transcription factors and leads to the activation of genes encoding proteins required for DNA replication (Egelkrout et al, 2001;Desvoyes et al, 2006).…”
mentioning
confidence: 99%